2020
DOI: 10.22277/rgo.v14i1.5658
|View full text |Cite
|
Sign up to set email alerts
|

Estratégias De Ensino Praticadas Nas Instituições De Ensino Superior Privada De Um Grupo Educacional Do Brasil Frente a Pandemia Do Covid-19

Abstract: O objetivo do estudo foi investigar as estratégias de ensino praticadas nas Instituições de Ensino Superior Privadas de um Grupo Educacional do Brasil em decorrência da pandemia do COVID-19. A pesquisa adotou abordagem quantitativa e utilizou questionário fechado enviado para 60 gestores das Instituições de Ensino Superior Privadas (IESsP) de um Grupo Educacional do Brasil (GEB) como instrumento de coleta dos dados. O estudo relata que as IES do GEB já tinham adotado 20% em ensino a distância e ao implantar au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
0
5
0
7
Order By: Relevance
“…For Oliveira et al (2020), it is possible to lead students to adopt a more active and autonomous attitude in their learning process. On the other hand, the few studies conducted so far about teaching in ERT (Bozkurt & Sharma, 2020;Oliveira et al, 2020) point to the need for digital training for teachers and to authors that share few experiences (Castaman & Rodriguez, 2020;Ribeiro & Corrêa, 2020).…”
Section: Emergency Remote Teaching: What We Have Learned So Farmentioning
confidence: 99%
See 1 more Smart Citation
“…For Oliveira et al (2020), it is possible to lead students to adopt a more active and autonomous attitude in their learning process. On the other hand, the few studies conducted so far about teaching in ERT (Bozkurt & Sharma, 2020;Oliveira et al, 2020) point to the need for digital training for teachers and to authors that share few experiences (Castaman & Rodriguez, 2020;Ribeiro & Corrêa, 2020).…”
Section: Emergency Remote Teaching: What We Have Learned So Farmentioning
confidence: 99%
“…Although studies of online TL are growing, there is much about the advancement and effectiveness of these experiences that are yet to be explored (Cranton & Torrisi-Steele, 2021;Wang, Torrisi-Steele, & Reinsfield, 2021). We are going through a stressful context that could affect faculty's and students' engagement (Bozkurt & Sharma, 2020); individual technology needs could become barriers to learning; most faculty have not been trained to teach remote classes (Castaman & Rodriguez, 2020;Oliveira et al, 2020;Ribeiro & Corrêa, 2020); and there are lessons to be drawn about the relationship between the pandemic and sustainability issues (Abeydeera, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There were few publications that analyzed the emergency remote teaching in Brazilian Universities (De la Fuente et al, 2021;Quispe-Pietro et al, 2021;Ribeiro & Corrêa, 2021), this can be based on two assumptions: 1) It is the rst time the universities are experiencing this type of drasctic change on teaching setup, called Emergency Remote Teaching (ERT), which differs from the Distance Education, ofering a temporarty instructional support and developted with a reduced planning time (Hodges et al, 2020;Mohmmed et al, 2020;Whittle et al, 2020). 2) It is observed that the research focused on the impact of ERT, and directed to the Education literature, has not used psychometric procedures with an approach focused on latent trait theory and without validation performed with the support of mental health measurement fundamentals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Diante dessa situação atípica e sendo preciso retomar o ano letivo, houve a mudança rápida para o ensino remoto e os estudantes se depararam com a necessidade de se adaptar, incluindo aqueles que até então tinham apenas experiências educacionais com o sistema de ensino presencial. Temos assim novos desafios com o novo formato de ensino, como o acesso às tecnologias digitais, as práticas pedagógicas, o assistencialismo social e de saúde (BRAUNER et al, 2020;RIBEIRO;CORRÊA, 2021), além da necessidade de os estudantes se manterem ativos em suas formações educacionais e profissionais.…”
Section: "Confieso Que": Un Estudio Sobre Barreras Autogestión Y Expe...unclassified